Accelerated 23-h enhanced recovery protocol for colon surgery: the CHASE-study - Thaís T. T. Tweed; Misha A. T. Sier; Imane Daher; Maikel J. A. M. Bakens; Johan Nel; Nicole D. Bouvy; James van Bastelaar; Jan H. M. B. Stoot (Scientific Reports, 2022)
Abstract The introduction of the Enhanced Recovery After Surgery (ERAS) program has radically improved postoperative outcomes in colorectal surgery. Optimization of ERAS program to an accelerated recovery program may further improve these said outcomes. This single-center, prospective study investigated the feasibility and safety of a 23-h accelerated enhanced recovery protocol (ERP) for colorectal cancer patients (ASA I–II) undergoing elective laparoscopic surgery. The 23-h accelerated ERP consisted of adjustments in pre-, peri- and postoperative care; this was called the CHASE-protocol. This group was compared to a retrospective cohort of colorectal cancer patients who received standard ERAS care. Patients were discharged within 23 h after surgery if they met the discharge criteria. Primary outcome was the rate of the successful discharge within 23 h. Successful discharge within the CHASE-cohort was realized in 33 out of the 41 included patients (80.5%). Compared to the retrospective cohort (n = 75), length of stay was significantly shorter in the CHASE-cohort (p = 0.000), and the readmission rate was higher (p = 0.051). Complication rate was similar, severe complications were observed less frequently in the CHASE-cohort (4.9% vs. 8.0%). Findings from this study support the feasibility and safety of the accelerated 23-h accelerated ERP with the CHASE-protocol in selected patients.